Pengembangan Modul Matematika Berbasis Inkuiri Terbimbing Materi Bangun Datar Kelas IV SDN 12 Pangkalpinang - Novita, Novita; Fitri Apriani; Sisi Pitriyana (Universitas Muhammadiyah Bangka Belitung, 2024)
This research is motivated by the lack of use of teaching materials in schools which are still not effective because the materials are instant. The aim of the research is to determine the characteristics of the Guided Inquiry-Based Mathematics Module teaching materials that are valid, practical and effective in plane material. This type of research is an ADDIE development model (Analyze, Design, Development, Implementation and Evaluation. The data collection techniques and instruments used are observation, interviews, questionnaires and tests. This research produces Guided Inquiry Based Mathematics Module teaching materials which are very valid). '', ''very practical'' and